Marginally trapped submanifolds in Lorentzian space forms and in the Lorentzian product of a space form by the real line - Anciaux, Henri (2015)
We give local, explicit representation formulas for n-dimensional spacelike submanifolds which are marginally trapped in the Minkowski space R1 n+2 , the de Sitter space dSn+2, the anti-de Sitter space AdSn+2 and the Lorentzian products Sn+1 × R and Hn+1 × R of the sphere and the hyperbolic space by the real line.